(untitled) - Katzung, Bertram G. (Norwalk, Connecticut, 1993)
Short discussion of the major concepts that underlie basic principles or specific drug groups. Explanatory figures and tables. Review questions followed by answers and explanations. Drug trees in drug-oriented chapters that visually organize drug groups. A list of high-yield terms and definitions you need to know. Skill Keeper Questions that prompt you to review previous material to understand links between related topics. A checklist of tasks you should be able to perform upon completion of a chapter. Summary tables that list the important drugs and include key information about their mechanisms of action, effects, clinical uses, pharmacokinetics, drug interactions, and toxicities.
Keywords: Pharmacology,Dược vật học